Numerical analysis of shell and tube heat exchanger with combination of different baffles - Muhammad Waleed; Syed Murawat Abbas Naqvi; Hammad Mustafa; Mohammed K. Al Mesfer; Mohd Danish; Kashif Irshad; Hasan Shahzad (Case Studies in Thermal Engineering)
Shell and tube heat exchangers (STHXs) are special systems that transfer thermal energy, and they have a significant position in numerous industries. The structure and arrangement of baffles play a vital role in boosting heat transfer rate, increasing thermo-hydraulic performance, and reducing the pumping cost. The numerical study is based on computational fluid dynamics (CFD) to run and investigate 3-D turbulent flow in the STHXs and the thermal performances of two unique combinations of baffles. The combination of double and triple flower baffles (COMB-A) and the combination of triple and novel quadruple flower baffles (COMB-B) are compared with double flower baffle (DFB) and triple flower baffle (TFB). The numerical model of STHX with segmental baffles (SGB) shows promising results while validating it with the previously published results. In the same way, the thermo-hydraulic performances of DFB-STHX, TFB-STHX, COMB-A STHX, and COMB-B STHX are evaluated and then compared. Based on numerical results, the heat transfer rate of COMB-B STHX is greater than DFB-STHX by 6.80 % and 10.76 % than the TFB-STHX. The pressure drop on the shell side for two novels STHXs i.e. COMB-A STHX and COMB-B STHX is reduced by 7.74 %, and 9.39 %, respectively, as compared to DFB-STHX. The comprehensive performance of COMB-A STHX and COMB-B STHX is better than that of the STHX with common flower baffles by 4.16 % and 8.16 % respectively. On the shell side, the fluid flow behavior in COMB-A STHX and COMB-B STHX improves the interaction between cold and hot fluids to optimize thermo-hydraulic performance.